Isolation and identification of leukocyte populations in intracranial blood collected during mechanical thrombectomy. Issue 2 (February 2022) - Shaw, Benjamin C; Maglinger, G Benton; Ujas, Thomas; Rupareliya, Chintan; Fraser, Justin F; Grupke, Stephen; Kesler, Melissa; Gelderblom, Mathias; Pennypacker, Keith R; Turchan-Cholewo, Jadwiga; Stowe, Ann M
Using standard techniques during mechanical thrombectomy, the Blood and Clot Thrombectomy Registry and Collaboration (BACTRAC) protocol (NCT03153683) isolates intracranial arterial blood distal to the thrombus and proximal systemic blood in the carotid artery. We augmented the current protocol to study leukocyte subpopulations both distal and proximal to the thrombus during human stroke (n = 16 patients), and from patients with cerebrovascular disease (CVD) undergoing angiography for unrelated conditions (e.g. carotid artery stenosis; n = 12 patients). We isolated leukocytes for flow cytometry from small volume (<1 mL) intracranial blood and systemic blood (5–10 mL) to identify adaptive and innate leukocyte populations, in addition to platelets and endothelial cells (ECs). Intracranial blood exhibited significant increases in T cell representation and decreases in myeloid/macrophage representation compared to within-patient carotid artery samples. CD4 + T cells and classical dendritic cells were significantly lower than CVD controls and correlated to within-patient edema volume and last known normal. This novel protocol successfully isolates leukocytes from small volume intracranial blood samples of stroke patients at time of mechanical thrombectomy and can be used to confirm preclinical results, as well as identify novel targets for immunotherapies.